Analisis Potensi Penerapan Sistem Transportasi Berbayar terhadap Kinerja Lalu Lintas Perkotaan - Bunyamin, Bunyamin; Saputra, Romi; Pramanda, Heru; Ridha, Muhammad; Muammar, Rajib (Lembaga Teewan Journal Solutions, 2026)
Banda Aceh serves as a center for economic, commercial, educational, and governmental activities, resulting in high traffic mobility that potentially causes congestion, particularly in shopping district areas. One of the roads experiencing significant traffic density is Jalan KH. Ahmad Dahlan due to the intensive use of private vehicles and on-street parking activities despite the availability of parking facilities. This condition highlights the need for a paid transportation policy through the implementation of Electronic Road Pricing (ERP) as a traffic management strategy. This study aims to analyze road users’ perceptions regarding the implementation of ERP and the potential shift from private vehicles to the Trans Koetaradja mass public transportation system. The research employed a survey method through interviews with private vehicle users traveling along the study corridor. The findings indicate that 36% of respondents are willing to shift to Trans Koetaradja buses, 64% prefer to use alternative routes, and only 18% would continue using private vehicles on the road segment. This study is expected to provide valuable input for policymakers in formulating sustainable urban traffic congestion management strategies.